Influence of the para-Substituent in Lanthanoid Complexes of Bis-Tetrazole-Substituted Calix[4]arenes - Phe, Rene; Skelton, B.W.; Massi, Max; Ogden, Mark (WILEY-V C H VERLAG GMBH, 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim 5,11,17,23-Tetra-tert-butyl-25,27-dihydroxy-26,28-bis(tetrazole-5-ylmethoxy)calix[4]arene has been reported to form remarkable Ln19 and Ln12 elongated clusters, upon addition of aqueous ammonium carboxylates. The impact of the para substituent on lanthanoid cluster formation has been studied by synthesising two new bis-tetrazole calixarenes, with p-H, and p-allyl substituents. Solution phase dynamic light scattering measurements of the reaction mixtures indicated that clusters are not formed with the p-H and p-allyl derivatives, in contrast with the behaviour of the tert-butyl analogue. Lanthanoid complexes of the p-H and p-allyl calixarenes were characterised by single-crystal X-ray diffraction, and were found to form mononuclear complexes, linked to form a one-dimensional coordination polymer for the p-allyl system. All of the complexes were isolated as ammonium salts, with ammonium cation included in the calixarene cavity in most cases. It is concluded that the nature of the para substituent has a profound impact on the lanthanoid cluster formation process, and derivatives with more subtle structural changes will be required to determine if additional lanthanoid “bottlebrush” clusters can be isolated.